Curriculum Development: The Journey of Bangladesh College of Physicians and Surgeons - Shamsad, Iffat Ara; Siddique, Md Ibrahim; Bari, Md Shafiqul; Ara, Iffat; Hussain, Md Margub; Hasan, Mahmud (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Bangladesh College of Physicians and Surgeons has been the pioneer in developing post-graduate medical education in this country. The curriculum offers guidelines for selecting versatile candidates to become future specialist, training particulars and learning outcomes and set criteria expected of them at the exit. In general, the curriculum is the guideline for the trainees and training facilities including the assessment system to fulfill the conditions to facilitate creation of specialist in different disciplines To document the hard works done by the fellows in last 50 years to establish curriculum in different specialities. All the available data regarding development of curriculum found are analyzed to document the struggles did previously to develop curriculum in different specialities of BCPS. FCPS part-1 syllabus was printed in different subject in the year 2000. Between 2000-2005 most of the subject developed printed part-I syllabus. Changes in the structure of postgraduate medical education and training of the BCPS was initiated in 2012 by holding a workshop to discuss the way forward with participation of experts from the Royal College of Physicians and Surgeons of Glasgow, College of Physicians and Surgeons of Pakistan, experts from the USA together with leading members of the Faculties of BCPS. This resulted in the decision that individual Faculties need to develop a curriculum. To ensure competency based training a common frame work was approved by the Council of the College in 2016. In 2017 another important change was approved that FCPS course will be for 5 years from January 2020. On the back ground of those decisions of the council curriculum and log book development committee work hard to developed new curriculum and log book. Several Workshops involving leading Faculty members on the development of the curriculum were held in the following months starting on 2019. In the year 2020 and 2021 this committee with the help and different faculties and administration able to published new curriculum in 42 specilities. Dynamicity of the curriculum makes it possible to incorporate recent advancements in the subject. This updated curriculum includes relevant new developments in different specialties. J Bangladesh Coll Phys Surg 2022; 40: 74-77